„It is important to the people that it is working, not that they participate“ - Achievements in spatial research regarding civil participation - Fischer, Tatjana; Peer, Verena (Momentum Quarterly, 2013)
Civil Participation serves the promotion of emancipated citizens but also the search for alternative and cost-friendly solutions regarding the services of general interest. Foremost in rural areas the gap between expectations concerning the enhancement of quality of life and the real possibilities widen. On the example of empirical investigations in the field of spatial research the role of participation in the development of rural communities in Austria has been surveyed. The research focuses on a) the discrepancy between type, necessity and quality of participation processes with different stakeholder groups; b) the question if participation leads to an increase in quality of life for all. The paper concludes that it is important to the inhabitants that „things are working“ and that they can participate.
Keywords: spatial research; participation; quality of life; stakeholders